Peran Guru Bimbingan dan Konseling dalam Meningkatkan Kesadaran Kesehatan Mental Siswa di Yogyakarta - Yuni Dwi Lestari; Eko Perianto (Universitas Mathla'ul Anwar Banten, 2026)
This study aims to describe the role of Guidance and Counseling teachers in increase students' mental health awareness in Yogyakarta. Mental health is a fundamental aspect in early adolescent development who experience various biological, cognitive, and socio-emotional changes. Guidance and Counseling teachers have a strategic position as facilitators of student development through preventive, curative, and collaborative services. This research used a qualitative approach. Data collection techniques were conducted through in-depth interviews, observation, and documentation. Data analysis used data reduction, data presentation, and conclusions. Research informants consisted of one Guidance and Counseling teacher and eight seventh-grade students. The results showed that Guidance and Counseling teachers carry out their roles through: (1) preventive approaches with innovative classical services; (2) curative approaches through individual counseling and collaboration with psychology; and (3) collaborative approaches by establishing intensive communication with homeroom teachers, subject teachers, and parents